Design of concave capacitance sensor for void fraction measurement in gas-liquid flow - Lim, L.G. (Institute of Electrical and Electronics Engineers Inc., 2017)
Void fraction is an important parameter to be measured in gas-liquid flow. Several designs of two-electrodes capacitance sensor had been analyzed and optimized for void fraction measurement. The conventional two-electrode concave capacitance sensor showed high sensitivity but it was also the most affected by air-water distribution. Thus far, only two-electrodes concave design had been discussed. In this paper, the concave design is divided into two-, four-and six-electrode using finite element method. The sensitivity of the sensor, effect of air-water distribution and linearity of response are analyzed and compared. The numerical results showed that four-electrode concave sensor is more suitable than the conventional two-electrode for void fraction measurement in gas-liquid flow. © 2016 IEEE.